(3eYQaI ONhd GdYGe GdCYLei hCSeGA GdTghQ GdQhejI hGdSQjGfjI hGdbHWjI hGdYQHjI hYOJgGs
(3ChdgG (B:s
(3HGH eYQaI ONhd GdYGe GdCYLei hgh Cf JCNP eG RGO Ydi GdNeS eFI hJVja Edjg CQHYI G S Ke JSbW CSHGY SHYI SHYI s
(3BNQgG (B:s
(3hJHOC HGdYOO ef RMd hHYOg GdeTJQi hGdeQjN hGdTeS hGdRgQI hYWGQO hGdbeQ agPg SHYI aCjf eG JYOO YOO dg agh GdChd ef Pdc GdHQhL hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B9(3H (B- (3U(B15(3Cs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs